Sosialisasi dan Penanaman Tanaman Obat Keluarga (Toga) di SD Negeri 10 Pemecutan Kec. Denpasar Barat Kota Denpasar - Arta, Dewa Gede Sumber; Bestari, Ni Made Prasiwi (Jurnal Pengabdian Masyarakat, 2026)
The Community Service Program (KKN) organized by the National University of Education carried the theme "Eco Smart Community" and took place from January 12 to February 27 in Pemecutan Village, West Denpasar District, Bali. One of the implemented work programs was "Health Education through Socialization and Planting of Family Medicinal Plants (TOGA) at SD No. 3 Pemecutan," which was conducted on January 23, 2026. This program aimed to foster understanding and awareness of health among elementary school students through an educational and participatory approach with an environmental perspectiveThe activity consisted of several stages: interactive socialization on the importance of maintaining health, introduction to the various types and benefits of Family Medicinal Plants (TOGA), and handson practice planting medicinal plants such as ginger, turmeric, aloe vera, and cocor bebek. School land that was previously underutilized was optimized to support these activities. The experiential learning method was applied so that students could learn directly through real experiences.The results of this activity showed an increase in students’ knowledge about the benefits of medicinal plants as an environmentally friendly and easily accessible health alternative. Furthermore, the vacant school land was successfully transformed into a simple TOGA garden, which not only holds educational value but also provides ecological benefits. This program contributes to realizing the concept of an eco-smart community through the sustainable use of local resources while instilling healthy living habits from an early age.